High performance electrospun nickel manganite on carbon nanofibers electrode for vanadium redox flow battery. (20th September 2020) - Busacca, C.; Blasi, O. Di; Giacoppo, G.; Briguglio, N.; Antonucci, V.; Blasi, A. Di
Highlights: A cost-effective NiMn2 O4 /CNF material is synthesized by electrospinning method for VRFB. A power density of 550 mW/cm 2 at 500 mA/cm 2 contributes reducing the cost for kW stack. The assembled battery shows an energy efficiency of 68% at 500 mA/cm 2 . The battery assembled with NiMn2 O4 /CNF shows a high active material utilization. The high reversibility is due to the morphology and structural defects of ternary metal oxide. Abstract: A composite material based on nickel manganite and carbon nanofibers (NiMn2 O4 /CNF) is synthesized by electrospinning method and investigated as a symmetric electrode for vanadium redox flow battery (VRFB). The X-ray diffraction pattern shows the formation of NiMn2 O4 /CNF, characterized by a cubic spinel-type structure and a high graphitization degree of the carbon nanofiber. XPS analysis reveals the presence of mixed oxidation state of nickel and manganese as Ni 2+ /Ni 3+ and Mn 2+/ Mn 3+, respectively. As evident by scanning electron microscope analysis (SEM), a complete covering of carbon nanofibers surface by NiMn2 O4 nanoparticles occurs. Charge-discharge curves are carried out from 80 mA/cm 2 up to 500 mA/cm 2 . The best result shows an energy efficiency (EE) of about 68% with corresponding deep of discharge (DoD) of about 55% at 500 mA/cm 2 . The high electrical conductivity as well as the high hydrophilicity, useful for improving the active surface area utilization, could be responsible for the remarkable results of the electrospun electrodes. In fact, thanks to the structural defects of the NiMn2 O4 /CNF and the presence of hydroxyl (OH), carboxyl (COOH) and nitrogen functional groups, the electrocatalytic activity increases at the electrode/electrolyte interface. Therefore, a remarkable power density at very high current density was achieved, 550 mW/cm 2 at 500 mA/cm 2 . Graphical abstract: Image, graphical abstract